Whole Genome Sequencing of Hulunbuir Short-Tailed Sheep for Identifying Candidate Genes Related to the Short-Tail Phenotype. Issue 2 (1st February 2018) - Zhi, Dafu; Da, Lai; Liu, Moning; Cheng, Chen; Zhang, Yukun; Wang, Xin; Li, Xiunan; Tian, Zhipeng; Yang, Yanyan; He, Tingyi; Long, Xin; Wei, Wei; et al.
Abstract: The Hulunbuir short-tailed sheep ( Ovis aries ) is a breed native to China, in which the short-tail phenotype is the result of artificial and natural selection favoring a specific set of genetic mutations. Here, we analyzed the genetic differences between short-tail and normal-tail phenotypes at the genomic level. Selection signals were identified in genome-wide sequences. From 16 sheep, we identified 72, 101, 346 single nucleotide polymorphisms. Selection signals were detected based on the fixation index and heterozygosity. Seven genomic regions under putative selection were identified, and these regions contained nine genes. Among these genes, T was the strongest candidate as T is related to vertebral development. In T, a nonsynonymous mutation at c.G334T resulted in p.G112W substitution. We inferred that the c.G334T mutation in T leads to functional changes in Brachyury—encoded by this gene—resulting in the short-tail phenotype. Our findings provide a valuable insight into the development of the short-tail phenotype in sheep and other short-tailed animals.